Can Comparing Traditional and Green Infrastructure Promote Cosystems Restoration? Case study of three Restoration Assessments in Cameroon (London Journal of Research In Science: Natural and Formal, 2025)
Much of Africas forest ecosystems heritage can be found in Cameroon. The country has since ratified numerous Conventions and enacted laws to protect and valorize these connecting ecosystems benefiting local people and global climate. These forest and non-forest ecosystems constitute Cameroons green infrastructure today. However, due to anthropogenic and natural processes, these ecosystems face degradation, thereby weakening their superstructure, diminishing their services value; threatening livelihoods, and contributing to climate change.We draw in this paper, parallels between green infrastructure and traditional (hard) infrastructure, in a bid to attract to ecosystems restoration, a comparable maintenance mindset, historically reserved for hard infrastructure. We use the prisms of three ecosystems assessments for restoration, as case studies. These are; (i) the northern savannah, (ii) Sanaga-Kadey watershed and (iii) the forest transition zones of Cameroon. By analyzing some common parameters across these ecosystems, including (i) land tenure, (ii) multifunctionality, (iii) climate resilience, (iv) critical resource use efficiency, (v) carbon neutrality, (vi) connectivity, (vii) stakeholder engagement, (viii) social inclusivity and (ix) maintenance-friendliness, we simultaneously make a case for adopting analogous maintenance mindsets towards securing and re-building Cameroons threatened green infrastructure.
Keywords: bivariate survival functions; dependence functions; biomedical applications; econometrics; bivariate Wiener and Pareto stochastic processes construction; dark energy.; PLANCK time; age of the universe; Cameroon; inclusiveness; Green infrastructure; ecosystem restoration